IMPRОVING WRITING SKILLS TО ЕNHАNCЕ STUDЕNTS’ LЕАRNING - Murаdоv Utkir Nurillаyеvich; Rаhimjоnоvа Khumоrа Ziyоvuddin qizi (Educational Research in Universal Sciences, 2024)
Enhancing students’ learning outcomes through the improvement of writing skills is a critical aspect of education. This article explores the importance of developing students’ writing abilities to help them effectively convey their thoughts and ideas. By providing opportunities for practice, feedback, and integration of writing assignments across disciplines, educators can empower students to become more effective communicators and critical thinkers. Ultimately, prioritizing the improvement of writing skills in the curriculum can lead to enhanced learning experiences and academic success for students.